Exploring the Effects of Coffee Shop Brand Experience on Loyalty: The Roles of Brand Love and Brand Trust - Raden Bernard Eka Hutomo Putra Maduretno; M.F. Sheellyana Junaedi (Gadjah Mada International Journal of Business, 2022)
Loyalty is an essential asset for a particular brand to maintain excellent relationships with its customers and secure its continuing long-term business. An understanding customers' emotional and rational dimensions regarding brand performance is required to collect information to develop a great brand management strategy. Therefore, this study examines mediating roles of both brand love and brand trust in relation to the dimensions of brand experience (sensory, affective, intellectual, and behavioral) and brand loyalty in the coffee shop business context. A total of 225 valid questionnaires were collected from Generation Z (Gen Z) and Y (Gen Y) coffee consumers in Yogyakarta, Indonesia. The Partial Least Squares Structural Equation Modeling (PLS-SEM) was selected as an analytical method to evaluate the research results. The results show that affective, intellectual, and behavioral experiences directly influence brand love and brand trust, while the sensory experience only affects brand love. Furthermore, brand love and brand trust are proven to have a direct influence on brand loyalty. Subsequently, brand love successfully mediates the effect of each dimension of brand experience on brand loyalty. In contrast, brand trust is not successful in mediating the effect of sensory experience on brand loyalty. The results also clearly show that none of the model coefficient paths are significantly moderated by generation due to the small age gap. Finally, the findings suggest what all factors that could enhance brand loyalty to achieve competitive advantages and develop marketing strategies are. Limitations and further research are also discussed.